A Comparison of Nine Counterfactual Theories of Causation Using Seven Examples. - Grenda, Vytautas (Problemos, 2009)
The article compares and evaluates nine last-decade counterfactual theories of singular causation, which were either created or inspired by David Lewis, Joseph Y. Halpern and Judea Pearl and presented in the texts of six other authors. Some differences between those theories that have not yet been described in literature are shown in the article. It is argued that the majority of those theories analyze intuitively similar examples in different ways. In that respect, those theories impose distinctions which, according to the folk theory of causation, are (and should be) absent.